2021
DOI: 10.4194/1303-2712-v21_7_03
|View full text |Cite
|
Sign up to set email alerts
|

n-3 LC-PUFA Enrichment Protocol for Red Earthworm, Eisenia fetida: A Cheap and Sustainable Method

Abstract: This study assessed the potential of omega-3 long chain polyunsaturated fatty acids (n-3 LC-PUFA) enrichment in red earthworm (Eisenia fetida, REW), via the addition of fish oil (FO, anchovy oil) to the culture-compost. FO addition to compost was tested at graded inclusion doses (0, 2.5, 5 and 10 g/100 g compost) and for different timeperiods, up to 96h. Dose, time, as well as dose and time interactions of FO compost enrichment had significant effects on all fatty acids of earthworm bodies. The enrichment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The latter is consistent with the literature which has reported that E. fetida can rapidly enrich themselves with long-chain polyunsaturated fatty acids with maximal uptake after only 24 h . On the other hand, in slice (d), which includes contributions from both the stomach and head region, the −CHCH- CH 2 -CHCH– peak is not as large, consistent with the process mainly occurring in the stomach.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The latter is consistent with the literature which has reported that E. fetida can rapidly enrich themselves with long-chain polyunsaturated fatty acids with maximal uptake after only 24 h . On the other hand, in slice (d), which includes contributions from both the stomach and head region, the −CHCH- CH 2 -CHCH– peak is not as large, consistent with the process mainly occurring in the stomach.…”
Section: Resultssupporting
confidence: 91%
“…This suggests that either the unsaturations are being synthesized from 13 C enriched algal components and/or polyunsaturated species/moieties are being concentrated from the food source. The latter is consistent with the literature which has reported that E. fetida can rapidly enrich themselves with long-chain polyunsaturated fatty acids with maximal uptake after only 24 h. 48 On the other hand, in slice (d), which includes contributions from both the stomach and head region, the −CH�CH-CH 2 -CH�CH− peak is not as large, consistent with the process mainly occurring in the stomach. In slice (e), which includes the stomach and clitellum, the peak in the green box (associated with CH 3 groups) is larger than that in the blue box.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…This could be attributed to poor growth and increased chitin content (non-digestible protein) in diet T6 due high inclusion levels of E. fetida that could have decreased its digestibility (Musyoka et al, 2019). Thus, reduced supply of nutrients for development and enhanced stress tolerance in C. gariepinus larvae (Kumlu et al, 2021). Furthermore, high stress indices were recorded possibly because lipid (10.4/% dry matter) content could have increased PUFA beyond optimal levels for C. gariepinus larvae and could have caused physiological malfunctioning and suppression of stress management abilities of the larvae (Rufchaei et al, 2019).…”
Section: A Comparison Of Weeks Four-and Six-old C Gariepinus Larvae S...mentioning
confidence: 99%
“…Yet, information from such evaluations could contribute to the development of aquafeeds that guarantee fish larvae health and quality. This is because nutritional content in a diet has proportionate effects on fish larvae growth, immunity, and general robustness (Kreutz et al, 2008;Kumlu et al, 2021). This study aimed at determining the effects of partially replacing C. nilotica with S. platensis or E. fetida on stress tolerance of C. gariepinus larvae.…”
Section: Introductionmentioning
confidence: 99%